Raymund L. Zwemer papers - Zwemer, Raymund L. (Raymund Lull), 1902-1981.
Correspondence, speeches and writings, professional and organizational files, appointment diaries, personnel records, printed matter, and other papers documenting Zwemer's career as professor of anatomy at Columbia University and in administrative and advisory positions at the Library of Congress, Unesco, U.S. State Dept., and other scientific institutions. His associations with the American Institute of Biological Sciences, Federation of American Societies for Experimental Biology, and American Association of Anatomists are reflected in the collection as are his research interests in the function of the adrenal glands, cortisone, the biological effects of potassium, and focused ultrasound.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Biologist, educator, and scientific administrator. Died 1981.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American Association of Anatomists; American Institute of Biological Sciences; Columbia University -- Faculty; Federation of American Societies for Experimental Biology; Library of Congress; Unesco; United States. -- Department of State; Adrenal glands; Anatomy -- Study and teaching; Biology -- Research; Cortisone; Potassium -- Physiological effect; Ultrasonics; Biologists; Educators; Administrators